STRENGTHENING CYBER SECURITY IN PORT FACILITIES: NEW THREATS AND MITIGATION STRATEGIES - Saputra, Toto Dwijaya; Marsudi, Sugeng (IJMEA International Journal of Marine Engineering and Applications, 2026)
The development of digital technology and automation in port facilities increases the risk of cyberattacks that can disrupt logistics operations and maritime security. According to a recent report, 72% of port facilities in Indonesia have experienced attempted cyberattacks in the past three years, with potential losses reaching USD 5.2 million per incident. This study aims to analyze cyberthreats in port facilities and evaluate mitigation strategies. The research method used was descriptive quantitative, with data collected through a survey of 120 port security officers, interviews with 15 operational managers, and an analysis of 10 related cybersecurity policy documents. The results showed that 68% of facilities had a moderate to low level of cybersecurity readiness, 74% of respondents emphasized the importance of human resource training, and 63% of facilities had not implemented a real-time intrusion detection system. Recommended mitigation strategies include the implementation of comprehensive network security protocols, multi-layered digital surveillance, and regular training programs for all personnel. These findings emphasize the urgency of integrating cybersecurity policies with daily port operations to reduce the risk of disruption, improve operational reliability, and minimize economic losses.